2009
DOI: 10.1258/acb.2009.008213
|View full text |Cite
|
Sign up to set email alerts
|

Serial increased cardiac troponin T predicts mortality in asymptomatic patients treated with chronic haemodialysis

Abstract: Background: A single detectable cardiac troponin predicts mortality in patients treated with dialysis. There are limited data on changes in troponin concentration over time and the clinical implications of serial troponin measurement. Methods: Serial cardiac troponin T (cTnT) was assayed five times over 12 months in a prospective cohort study of patients with end-stage kidney disease treated with haemodialysis. A concentration of cTnT !0.04 mg/L was considered increased. Mortality and cardiovascular events wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
3
23
1
Order By: Relevance
“…In the current study, a lack of correlation between SBP, DBP and cTnT elevation on all-cause mortality indirectly confirms the results of Velasco et al [23], suggesting that large interdialytic weight gains requiring increase of UF lead to greater intra-and post-dialytic BP drops, which most likely are as unfavorable as increased but stable BP. Our finding of no direct correlation between cTnT, OH% and the incidence of AMI (only a tendency for cTnT) is in contrast to previous studies [16,24] . A previous study by Pianta et al [25] revealed no relationship between cTnT and left ventricle mass parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, a lack of correlation between SBP, DBP and cTnT elevation on all-cause mortality indirectly confirms the results of Velasco et al [23], suggesting that large interdialytic weight gains requiring increase of UF lead to greater intra-and post-dialytic BP drops, which most likely are as unfavorable as increased but stable BP. Our finding of no direct correlation between cTnT, OH% and the incidence of AMI (only a tendency for cTnT) is in contrast to previous studies [16,24] . A previous study by Pianta et al [25] revealed no relationship between cTnT and left ventricle mass parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies showed that older generations of cTnT assays were prognostic of mortality in patients with reduced eGFR or ESRD. [7][8][9][10][11][12][13][14] Studies of patients with reduced eGFR and an acute coronary syndrome or presenting to an emergency room with chest pain also showed an increased risk of death in those with an elevated cTnT compared with a cTnT below the established necrosis limit. [15][16][17] Older studies typically defined an elevated cTnT as $0.09 ng/ml and found roughly a 2.6-fold increased risk of death in those with an elevated cTnT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, by measuring cTn concentrations every two months, for a period of 6 months an additional number of patients with elevated cTn concentrations (at least once during the follow-up) could be identified (Jacobs et al, 2009 and interestingly the patient survival decreased with increasing occurrence of cTnT elevations, i.e. the 1.7 year patients survival was 100%, 90% and 78% for patients with zero, one to four, or five out of five concentrations (Roberts et al, 2009). These findings are in line with above mentioned prognostic value of cTn elevations in ESRD patients.…”
Section: Fig 3 (A)mentioning
confidence: 99%